2020
DOI: 10.5664/jcsm.8114
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic activity is reduced during slow-wave sleep, but not resting wakefulness, in patients with chronic fatigue syndrome

Abstract: Study Objectives: Physiological dearousal characterized by an increase in parasympathetic nervous system activity is important for good-quality sleep. Previous research shows that nocturnal parasympathetic activity (reflected by heart rate variability [HRV]) is diminished in individuals with chronic fatigue syndrome (CFS), suggesting hypervigilant sleep. This study investigated differences in nocturnal autonomic activity across sleep stages and explored the association of parasympathetic activity with sleep qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…These terms were also excluded due to their broad nature, although this may have resulted in potentially relevant articles not being captured. Some studies also utilised components of polysomnography including EEG and discussed features of sleep but did not undergo the whole polysomnography process [ 39 ]. Additionally, two studies by Neu et al were not included in this review due to not containing any key words in the abstract or title [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These terms were also excluded due to their broad nature, although this may have resulted in potentially relevant articles not being captured. Some studies also utilised components of polysomnography including EEG and discussed features of sleep but did not undergo the whole polysomnography process [ 39 ]. Additionally, two studies by Neu et al were not included in this review due to not containing any key words in the abstract or title [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…LF power is a compound regulatory function of the sympathetic nerve and vagus nerve, which further reflects the heart rate changes caused by baroreceptor reflex and blood pressure regulation [32]. Some research reported that HF and LF were significantly reduced in patients with chronic fatigue syndrome (CFS) or anxiety, which discovered there were an imbalance of cardiac autonomic nerves and the decreased cardiac vagus function in some mental illness [33,34]. Moreover, a recent study reported the average heart rate was increased in patients with depression [35].…”
Section: Discussionmentioning
confidence: 99%
“…In order to fall asleep, autonomic balance must switch to a parasympathetic dominant, recuperative mode, and the degree to which this is achieved is closely associated with a perception of good quality and refreshing sleep (Cvejic et al, 2018;Patel et al, 2013). We have previously documented that distress and ill health impede adequate induction of parasympathetic (vagal) activity leading, physiologically, to hypervigilant sleep that is typically reported as poor in quality and that impacts negatively on daytime functioning (Burton et al, 2010;Cvejic et al, 2017;Fatt et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient and poor quality sleep have been associated with physical and mental health problems, higher stress levels, burnout and reduced empathy, as well as drug and alcohol use (Lund et al, 2010;Wolf and Rosenstock, 2017). In addition, sleep impacts on cognitive performance and has a bidirectional link with autonomic and immune function (Cvejic et al, 2018;Fatt et al, 2019;Irwin, 2015). The autonomic nervous system (ANS) plays a complex role in the maintenance of physical and mental health (Beaumont et al, 2012;Thayer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation